Distributed Denial of Service Attack Detection Techniques for Mobile Ad Hoc Networks - Chaudhary, A; Shrimal, G; Rautela, R (International Journal of Computer Sciences and Engineering, 2025)
Nowadays, Mobile ad hoc networks are very attractive in terms of its flexibility because there is no need of predefined infrastructure for communication such as wired network. This flexibility makes mobile ad hoc network more vulnerable to threats. Threats compromise with the attributes of security so reason being threats can be decreased the survivability or performance of the mobile ad hoc networks. Several types of attacks in MANETs have been reviewed in the literature, the most popular attack is Distributed Denial of Services Attack (DDoS) because the aim of DDoS is to restrict the MANETs to provide the normal services to their intended users by consuming bandwidth or overload the resources. This paper focuses on the several detection techniques of DDoS attack and proposed a new technique based on genetic algorithm for the detection of DDoS attack on MANETs